2019
DOI: 10.1159/000502399
|View full text |Cite
|
Sign up to set email alerts
|

Three Patients with Lithium-Associated Hyperparathyroidism: Literature Review Regarding Medical and Surgical Management

Abstract: Lithium (Li) carbonate has been established as a mood stabilizer and an efficacious treatment for bipolar disorder since its discovery by Dr. John Cade in 1948. Li interacts significantly with organ systems and endocrine pathways. One of the most challenging side effects of Li to manage is its effect on the parathyroid glands. Dysregulation of parathyroid signaling due to Li results in hypercalcemia due to increased vitamin D3 generation, increased calcium absorption from the gut, and bone resorption, occasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Livingstone C et al [22] also revealed that PTH levels change through a similar mechanism. [39] Kidney related side effects occur in approximately 20% of patients after long-term treatment with lithium. [40] Hestbech et al [41] in a study conducted in patients with lithium intoxication, they revealed the development of chronic tubulointerstitial nephritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Livingstone C et al [22] also revealed that PTH levels change through a similar mechanism. [39] Kidney related side effects occur in approximately 20% of patients after long-term treatment with lithium. [40] Hestbech et al [41] in a study conducted in patients with lithium intoxication, they revealed the development of chronic tubulointerstitial nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…[43] The risk of chronic kidney damage occurring in the later stages of chronic lithium administration may contribute to the formation of hyperparathyroidism. [39] It has been reported that the cause of hypercalcemia that occurs may also be the result of hyperparathyroidism. [44] In this study, where subacute lithium was administration, we observed increased PTH and Ca levels similar to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Однако важно понимать, что литий токсически действует на все ОЩЖ, следовательно, риск рецидива после хирургического лечения крайне высок. C другой стороны, в связи с тем, что литий токсически действует на все ОЩЖ, терапия кальцимиметиками оправдана только при кратковременном приеме данных препаратов [16,35]. Bernstein J, et al было высказано предположение, что пациентам с бессимптомной гиперкальциемией или легкой гиперкальциемией целесообразно назначение цинакальцета, а пациентам с тяжелой гиперкальциемией -проведение паратиреоидэктомии [36].…”
Section: лечение гиперкальциемии ассоциированной с приемом препаратов...unclassified
“…There are other less frequent indications with an evidence level 4 grade C for: finding of causal lesions in lithiuminduced hyperparathyroidism [20], functional parathyroid cyst [21] and with an evidence level 2b grade B the followup pharmacological management with Cinacalcet [22].…”
Section: Indicationsmentioning
confidence: 99%